2020
DOI: 10.1002/essoar.10502240.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eddy saturation of the Southern Ocean: a baroclinic versus barotropic perspective

Abstract: Key Points:• An isopycnal layered model, with a varying number of fluid layers, is used to assess relative importance of barotropic and baroclinic processes in the Southern Ocean.• Both baroclinic and barotropic flows exhibit regimes in which mean zonal transport is insensitive to wind stress.• Eddies actively shape the time-mean flow, irrespective of the instabilities from which they originate.Abstract "Eddy saturation" is the regime in which the total time-mean volume transport of an oceanic current is relat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Our work contributes to its interpretation and strives to unravel the underlying causal chain of processes. Our results complement those of Barthel et al (2017), Constantinou et al (2019) and Patmore et al (2019) in drawing attention to the barotropic flow component. Although baroclinic instability is, in our simulations, what ultimately sets the ACC density structure and transport, the barotropic flow plays a key role in modulating the propensity of the eddies to relax baroclinicity.…”
Section: (3) Baroclinic Instability and (5) Acc Transport Sensitivitysupporting
confidence: 80%
See 2 more Smart Citations
“…Our work contributes to its interpretation and strives to unravel the underlying causal chain of processes. Our results complement those of Barthel et al (2017), Constantinou et al (2019) and Patmore et al (2019) in drawing attention to the barotropic flow component. Although baroclinic instability is, in our simulations, what ultimately sets the ACC density structure and transport, the barotropic flow plays a key role in modulating the propensity of the eddies to relax baroclinicity.…”
Section: (3) Baroclinic Instability and (5) Acc Transport Sensitivitysupporting
confidence: 80%
“…In turn, this affects the efficiency of baroclinic instability processes at releasing APE and limit the circumpolar transport. The role of the ACC barotropic component is a subject of active research and our work complements the recent studies of Patmore et al (2019) and Constantinou et al (2019) in this regard.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This hypothesis has been verified several times in numerical models, for example, by Hallberg and Gnanadesikan (), Meredith and Hogg (), Nadeau and Straub (), Marshall et al. (), and Constantinou and Hogg (), but only indications of it have been seen in observations (Böning et al., ; Chidichimo et al., ; Firing et al., ).…”
Section: Introductionmentioning
confidence: 82%
“…Our understanding about changes in eddy kinetic energy (EKE) has been greatly improved over the past decades with the advent of satellite altimetry and increasingly high‐resolution ocean models that resolve or permit eddies. Numerical simulations suggested that enhanced wind stress will cause an increase in the transient eddy activity over time that counteracts increases in the ACC transport, resulting in increases in EKE but no significant change to volume transport (Constantinou & Hogg, 2019; Hallberg & Gnanadesikan, 2006; Hogg et al., 2015; Marshall et al., 2017; Meredith & Hogg, 2006; Straub, 1993). This has become to be known as the “eddy‐saturation” hypothesis.…”
Section: Introductionmentioning
confidence: 99%